Epidemiology and aetiology of maternal parasitic infections in low- and middle income countries - Tom K. Roberts; Courtney A. Gravett; Prasad Palani Velu; Evropi Theodoratou; Thor A. Wagner; Jian Shayne F. Zhang; Harry Campbell; Craig E. Rubens; Michael G. Gravett; Igor Rudan (Edinburgh University Global Health Society, 2011)
There have been very few systematic reviews looking at maternal infections in the developing world, even though cutting maternal mortality by three quarters is United Nation's Millennium Development Goal number five. This systematic review has two aims. The first is to present the prevalence of parasitic infections in the developing world over the last 30 years and the second is to evaluate the quality and distribution of research in this field.